A incidência da lesão renal aguda e mortalidade após o infarto agudo do miocárdio: comparação entre os critérios AKIN e RIFLE - Rodrigues, Fernando Bruetto (2012)
Acute kidney injury (AKI) increases the risk of death after acute myocardial infarction (AMI). Recently, two new AKI definitions were proposed: Risk, Injury, Failure, Loss, and End-stage kidney disease (RIFLE) and Acute Kidney Injury Network (AKIN). There are no data comparing AMI-related AKIs diagnosed by both criteria. The purpose of this study is to compare the incidence and mortality of AKI diagnosed by RIFLE and AKIN in the AMI acute phase. In total, 1050 consecutive AMI patients were studied. AKI defined by RIFLE and AKIN occurred in 14.8% and 42.7% of patients, respectively, in the first 7 days of hospitalization. This difference resulted from the larger number of patients in AKIN stage 1 (36.2%) compared with the number in RIFLE stage Risk (9.6%, p < 0.001). Both AKI criteria were associated with an increased Adjusted Hazard Ratio (AHR) for 30-day and 1-year mortality. The subgroup of patients classified as non-AKI by RIFLE but as AKI by AKIN criteria showed an increased AHR for death (2.49; 95% confidence interval [CI] 1.37 4.51, p=0.003) at 30 days and at 1 year (1.99; 95% CI 1.20 3.31, p=0.008) compared with patients without AKI. In conclusion, AKIN has detected more AKI than RIFLE in the acute phase of AMI. Both definitions were associated with increased early and late mortality. Patients diagnosed with AKI by AKIN but not by RIFLE showed an increased AHR for early and late mortality.